PENGARUH SISTEM BUNYI BAHASA BALI TERHADAP KATA SERAPAN YANG DIHASILKAN - Dewa Ayu Dyah Pertiwi Putri (Universitas Warmadewa, 2025)
This study aims to determine the influence of the Balinese language sound system on loan words produced in the language. This study uses a qualitative approach with the observation method and is complemented by note-taking techniques. The data in this study are loan words that do not have equivalents in Balinese; therefore, these loan words are similar to their original words, merely experiencing sound changes according to the Balinese sound system and characteristics. Data are sourced from 10 informants who are native Balinese, especially those who belong to the Baby Boomer generation to ensure that informants are rarely exposed to, know, and master foreign language accents. The influence of the Balinese language sound system and characteristics on the loan words is significant. These significances are 1) changes in vowel sounds to pepet or schwa sounds, 2) the elimination of consonant sounds, 3) restructuring of sound structures, 4) the addition of nasal sounds, and 5) the separation of syllables with CC patterns into new forms. The loan words produced tend to place the tongue in a neutral position with a relaxed condition. The efficiency of sound is very noticeable in this process due to the weak and complex consonant omission.